The importance of role models and demographic context for senior women's work identity development - Sealy, Ruth; Singh, Val (Blackwell Publishing, 2010)
The lack of senior female role models continues to be cited as a key barrier to women's career success. Yet there is little academic research into the gendered aspects of role modelling in organizations, or the utility of role models at a senior level. The paper starts with a review of papers examining the construction of role models in organizational settings. This leads to the inclusion of two related areas – organizational demographics as the contextual factor affecting the availability of role models and how they are perceived, and work identity formation as a possible key explanatory factor behind the link between the lack of senior female role models and the lack of career progression to top organizational levels. The literature looking at social theories of identity formation is then considered from a gender perspective. The key gaps identified are that while the behavioural value of role models has been well documented, a better understanding is needed of how gender and organizational demography influence the role modelling process. Importantly, the symbolic value and possibly other values of female role models in the identity construction of senior women require further in-depth investigation. Finally, this review calls for a more integrated approach to the study of role models and work identity formation, pulling together literatures on organizational demography, the cognitive construal of role models and their importance for successful work identity formation in senior women.